A 2:1 randomized, open-label, phase II study of selinexor vs. physician's choice in older patients with relapsed or refractory acute myeloid leukemia. Issue 13 (10th November 2021) - Sweet, Kendra; Bhatnagar, Bhavana; Döhner, Hartmut; Donnellan, Will; Frankfurt, Olga; Heuser, Michael; Kota, Vamsi; Liu, Hongtao; Raffoux, Emmanuel; Roboz, Gail J.; Röllig, Christoph; Showel, Margaret M.; et al.
Abstract: Selinexor, a selective inhibitor of nuclear export, has demonstrated promising activity in patients with acute myeloid leukemia (AML). This randomized, phase II study evaluated selinexor 60 mg twice weekly ( n  = 118) vs. physician's choice (PC) treatment ( n  = 57) in patients aged ≥60 years with relapsed/refractory (R/R) AML. The primary outcome was overall survival (OS). Median OS did not differ significantly for selinexor vs. PC (3.2 vs. 5.6 months; HR = 1.18 [95% CI: 0.79–1.75]; p  = 0.422). Complete remission (CR) plus CR with incomplete hematologic recovery trending in favor of selinexor occurred in a minority of patients. Selinexor treated patients had an increased incidence of adverse events. The most common grade ≥3 adverse events were thrombocytopenia, febrile neutropenia, anemia, hyponatremia. Despite well-balanced baseline characteristics, there were numerically higher rates of TP53 mutations, prior myelodysplastic syndrome, and lower absolute neutrophil counts in the selinexor group; warranting further investigation of selinexor in more carefully stratified R/R AML patients. Registered trial: NCT02088541.